Онтогенез Hyacinthella azurea (Fenzl) Chouard в условиях культуры на юго-востоке Украины - Павлова, М.А. (Промышленная ботаника, 2003)
The data on the biomorphologic peculiarities of Hyacinthella azurea cultivated at the Donetsk Botanical Gardens are given. 3 periods of 7 age states of the species large life-cycle are described, and the dynamics of age spectrum of the introduced population, formed in the course of ontogeny, is characterized.